Fault-tolerant control of a compliant legged quadruped robot for free swinging failure. (February 2018) - Gor, Mehul M; Pathak, PM; Samantaray, AK; Yang, Jung Ming; Kwak, SW
Quadruped robots are designed to work in remote or hazardous environments which are unreachable or harmful for humans. In these situations, reliability and adaptability are the most critical issues for the quadruped robot. During the failure of any actuator, the performance of quadruped robot is severely affected. The failure can lead to joint locking or free joint. In the case of free joint, leg joint loses actuator torque and also the capability to support the robot body on the ground. Leg joint also loses resistance to external load and acts as a free rotating hanging link. This article presents strategies for controlling a compliant legged quadruped robot in the presence of free swinging failure. The strategy is motivated by the natural crawling by infants and adapted crawling by persons with specific disabilities. Bond graph has been used for dynamic modeling of the system. The control strategy has been tested both through simulations and experiments conducted on a prototype quadruped robot.